Expanding Thermal Plasma Chemical Vapour Deposition of ZnO:Al Layers for CIGS Solar Cells - K. Sharma; B. L. Williams; A. Mittal; H. C. M. Knoops; B. J. Kniknie; N. J. Bakker; W. M. M. Kessels; R. E. I. Schropp; M. Creatore (International Journal of Photoenergy)
Aluminium-doped zinc oxide (ZnO:Al) grown by expanding thermal plasma chemical vapour deposition (ETP-CVD) has demonstrated excellent electrical and optical properties, which make it an attractive candidate as a transparent conductive oxide for photovoltaic applications. However, when depositing ZnO:Al on CIGS solar cell stacks, one should be aware that high substrate temperature processing (i.e., >200°C) can damage the crucial underlying layers/interfaces (such as CIGS/CdS and CdS/i-ZnO). In this paper, the potential of adopting ETP-CVD ZnO:Al in CIGS solar cells is assessed: the effect of substrate temperature during film deposition on both the electrical properties of the ZnO:Al and the eventual performance of the CIGS solar cells was investigated. For ZnO:Al films grown using the high thermal budget (HTB) condition, lower resistivities, ρ, were achievable (~5 × 10−4 Ω·cm) than those grown using the low thermal budget (LTB) conditions (~2 × 10−3 Ω·cm), whereas higher CIGS conversion efficiencies were obtained for the LTB condition (up to 10.9%) than for the HTB condition (up to 9.0%). Whereas such temperature-dependence of CIGS device parameters has previously been linked with chemical migration between individual layers, we demonstrate that in this case it is primarily attributed to the prevalence of shunt currents.